Turning antiferromagnetic Sm0.34Sr0.66MnO3 into a 140 K ferromagnet using a nanocomposite strain tuning approach. Issue 15 (29th March 2016) - Suwardi, Ady; Prasad, Bhagwati; Lee, Shinbuhm; Choi, Eun-Mi; Lu, Ping; Zhang, Wenrui; Li, Leigang; Blamire, Mark; Jia, Quanxi; Wang, Haiyan; Yao, Kui; MacManus-Driscoll, Judith L.
Abstract : Ferromagnetic insulating thin films of Sm0.34 Sr0.66 MnO3 (SSMO) on (001) SrTiO3 substrates with a T C of 140 K were formed in self-assembled epitaxial nanocomposite thin films. Abstract : Ferromagnetic insulating thin films of Sm0.34 Sr0.66 MnO3 (SSMO) on (001) SrTiO3 substrates with a T C of 140 K were formed in self-assembled epitaxial nanocomposite thin films. High T C ferromagnetism was enabled through vertical epitaxy of the SSMO matrix with embedded, stiff, ∼40 nm Sm2 O3 nanopillars giving a c / a ratio close to 1 in the SSMO. In contrast, bulk and single phase SSMO films of the same composition have much stronger tetragonal distortion, the bulk having c / a >1 and the films having c / a <1, both of which give rise to antiferromagnetic coupling. The work demonstrates a unique and simple route to creating ferromagnetic insulators for spintronics applications where currently available ferromagnetic insulators are either hard to grow and/or have very low T C .